Improvement of Falcataria moluccana Root Growth by Giving Empty Palm Oil Fruit Bunches (EFB) Biochar in Growing Media - Yunita, Repha Sera; Melya Riniarti; Wahyu Hidayat; Ainin Niswati; Hendra Prasetia; Udin Hasanudin; Irwan Sukri Banuwa; Eva Yunita; Falah Rizkasumarta (Journal of Sylva Indonesiana, 2023)
Sengon (Falcataria moluccana) is a fast-growing species widely planted in Industrial Plantation Forests (IPF/HTI) and has high economic value. The provision of planting material must be well prepared and planned to get the appropriate nursery planting media composition. The Empty Palm Oil Bunches (EFB) biochar application improves soil’s chemical and physical properties to provide nutrients for plants. This study aims to determine the effect of the application of EFB biochar on the growth of sengon roots. The experimental design was completely randomized (CRD) by applying four treatment levels and 20 repetitions. The treatments were (A) 100% soil (control), (B) 5% EFB biochar, (C) 10% EFB biochar, and (D) 15% EFB biochar. The data were then analyzed by analysis of variance to see the effect of the treatment on the observed root growth parameters, followed by the 5% Least Significant Difference (LSD) further test to determine differences between treatments. The parameters observed were root length, root volume, root wet weight, and root dry weight. The result showed that the application of EFB biochar increased the growth of sengon roots compared to the control. The greater the dose of the addition of EFB biochar given to the growing media, the more it showed a positive response in improving the growth of sengon roots. In this study, the 15% dose showed the best results compared to other treatments.